Analysis Of Tea Shoots Worth Processing (APLO) In The Raw Materials Of Orthodox Black Tea With Mechanical Picking Method At PT. Perkebunan Nusantara VIII Kebun Kertamanah Bandung, Jawa Barat - IMANNIANTY, AN-NISA; Juwitaningtyas, Titisari (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 10 No 3 (2022): SeptemberDO - 10.24843/JRMA.2022.v10.i03.p11, 2022)
T he aims of this study were (1) to identify the type and number of product defects in orthodox black tea raw materials at PT. Perkebunan Nusantara VIII Kebun Kertamanah (2) To find out the cause of defects in Orthodox Black Tea Raw Materials at PT. Nusantara VIII Plantation Kertamanah Plantation. The research method used is descriptive method with special study implementation methods. Data were analyzed using (1) analysis tables (2) Pareto diagrams (3) bar charts (4) cause-and-effect diagrams. The results obtained (1) the value of the percentage of tea shoots that are suitable for processing (2) the value of the percentage of shoots that do not meet the standards (3) the factors that cause the high percentage of shoots that do not meet the requirements at PT. Nusantara VIII Plantation Kertamanah Plantation